Keragaan Pertumbuhan dan Produksi Tiga Macam Jagung di Lahan Kering (Studi Kasus di Unitri Agroedupark Malang): Kata kunci: jagung, pertumbuhan, produksi, sifat tanah - Anggarbeni, Susilo Ribut; Murniyanto, Eko (innofarm, 2022)
Three types maize have been studied to measure growth and production in the dry land of Agroedupark Malang. This study is needed to obtain the types maize that tend to be suitable, in addition to land improvement if the three types of corn are to be developed in the same garden. The results showed that the three types of corn studied had growth performances similar to their descriptions, but purple sweet corn tended to be the best compared to white and hybrid varieties. However, the three types of corn studied had a production level of <50% of their potential production. It is recommended to use organic matter as an alternative in improving soil fertility so that corn productivity increases.